Global, regional, and national burden of non-communicable diseases attributable to occupational asbestos exposure 1990-2019 and prediction to 2035: worsening or improving? - Xinlu Miao; Teng Yao; Chenxian Dong; Zuhai Chen; Wanting Wei; Zhengyang Shi; Tongtong Xu; Jianjiang Shao; Qiang Niu; Dongsheng Rui; Yunhua Hu; Yizhong Yan (BMC, 2024)
Abstract Understanding the burden associated with occupational asbestos exposure on a global and regional scale is necessary to implement coordinated prevention and control strategies. By the GBD Study 2019, we conducted a comprehensive assessment of the non-communicable diseases burden attributable to occupational asbestos exposure. In 2019, 239,330 deaths and 4,189,000 disability-adjusted life years (DALYs) worldwide due to occupational asbestos exposure occurred. 1990-2019, deaths and DALYs attributed to occupational asbestos exposure increased by 65.65% and 43.66%, respectively. Age-standardized mortality rate (ASMR) and age-standardized DALYs rate (ASDR) decreased, with the most rapid declines in high Socio-Demographic Index (SDI) regions, with average annual percent change (AAPC) of − 1.05(95%CI: −1.2, −0.89) and −1.53(95%CI: −1.71, −1.36), respectively. Lung cancer, mesothelioma and ovarian cancer were the top three contributors to the increase in deaths and DALYs, accounting for more than 96%. AAPCs of ASMR and ASDR were positively associated with SDI. Global deaths from occupational asbestos exposure were predicted to increase and ASMR to decrease by 2035, mostly in males. Due consideration should be given to the susceptibility of the elderly, the lag of asbestos onset, and the regional differences, and constantly improve the prevention and control measures of occupational asbestos exposure and related diseases.